Real-World Clinical Experience on the Usage of High-Dose Metformin (1500-2500 mg/day) in Type 2 Diabetes Management - Ashok Kumar Das; Sanjiv Shah; Santosh Kumar Singh; Archana Juneja; Niroj Kumar Mishra; Arundhati Dasgupta; Nilakshi Deka; Mahesh Abhyankar; Santosh Revankar (Clinical Medicine Insights: Endocrinology and Diabetes, 2021)
Background: To evaluate the clinical characteristics, treatment patterns, and clinical effectiveness and safety of high doses of metformin (1500-2500 mg/day) in Indian adults with type 2 diabetes mellitus (T2DM). Materials and methods: A retrospective, multicentric (n = 241), real-world study included patients with T2DM (aged >18 years) receiving high doses of metformin. Details were retrieved from patient’s medical records. Results: Out of 5695 patients, 62.7% were men with median age was 50.0 years. Hypertension (67.5%) and dyslipidemia (48.7%) were the prevalent comorbidities. Doses of 2000 mg (57.4%) and 1500 mg (29.1%) were the most commonly used doses of metformin and median duration of high-dose metformin therapy was 24.0 months. Metformin twice daily was the most frequently used dosage pattern (94.2%). Up-titration of doses was done in 96.8% of patients. The mean HbA1c levels were significantly decreased post-treatment (mean change: 1.08%; P < .001). The target glycemic control was achieved in 91.2% patients. A total of 83.0% had decreased weight. Adverse events were reported in 156 patients. Physician global evaluation of efficacy and tolerability showed majority of patients on a good to excellent scale (98.2% and 97.7%). Conclusion: Clinical effectiveness and safety of a high-dose metformin was demonstrated through significant improvement in HbA1c levels and weight reduction.